Relation between O8 cluster shape and vibrational spectra in the ε-phase of solid oxygen. (9th August 2019) - Akahama, Yuichi; Fujihisa, Hiroshi; Hirao, Naohisa; Ohishi, Yasuo
Abstract: The relationship between shape distortion of the O8 cluster and vibrational spectra in the ε - phase of solid oxygen has been investigated via powder X-ray diffraction analysis, Raman scattering, and infrared (IR) absorption experiments at 297 K under high pressure. The pressure dependence of the lattice constant ratio a / b exhibited a minimum in the low-pressure region at ∼20 GPa, reflecting a decrease in the rhombohedral angle α of the O8 cluster. Based on the pressure evolutions of the vibrational spectra, nine Raman active and six IR active modes were identified as the fundamental vibrations. Raman and IR active stretching modes revealed an abnormal softening in the lower pressure region, which corresponded to the change in cluster shape. A clear relationship between the vibrational behavior and the shape of the cluster was revealed. These results were discussed from the perspective of the chemical bond in the cluster.